Hungarian Emerging - Diana Archangeli; Douglas Pulleyblank (Anuario del Seminario de Filología Vasca "Julio de Urquijo")
Phonological theories tend to focus on the end point of learning, the adult grammar, assuming some innate linguistic component determines the nature of the grammar that is acquired. In Emergent phonology, we explore the hypothesis that adult grammars take the shapes they have because they can be acquired; we go further and propose that there is no innate linguistic component for phonological acquisition. Given these hypotheses, grammars are acquired piecemeal and learners rapidly generalise over subparts of the lexicon. One prediction is that we expect languages to have regularities with widely differing effect – both general patterns and subpatterns that exist but only in a narrow domain. We test this hypothesis against Hungarian vowel harmony, a harmony pattern that is often described as involving both [back] harmony and [round] harmony, despite the fact that the language has nonharmonic suffixes, suffixes with limited harmony, disharmony, antiharmony, and both transparency and opacity. In particular, we discuss patterns of suffix alternation involving harmony. The patterns, morphologically determined, range from no alternation, to alternating only along the front-back dimension, to alternating in terms of both backness and rounding, to alternating in terms of backness, rounding and height.